Perception Paysanne Des Effets Du Changement Climatique Sur La Production Des Noix D’anacardier (Anacardium Occidentale L.) Dans La Commune De Savalou Au Bénin - Y. A, Tchétangni; A. E, Assogbadjo; T, Houéhanou; D. O, Bello (European Scientific Journal, ESJ, 2016)
This study aims to analyze the perception of farmers from the effects of climate change on the production of cashew nuts in the town of Savalou. Thus 210 farmers were surveyed in the Municipality of Savalou based on a semi-structured questionnaire. The data collected relate to the socio-cultural characteristics of the planters, their perception of the causes and weather events affecting the performance of the cashew tree and adaptation strategies. The results show that the majority of farmers have age less than 50 years. The age of the plantations, the average yield, density and performance achieved in 2014 varied significantly (P <0.05) from one district to another. Adults and youth sociocultural groups Nago, Mahi, and Ife have seen that climate change is the major constraint in the production of cashew nuts. As for the main climatic parameter affecting the production of cashew, the majority of farmers (80%) in this case, old Ife, Mahi and youth Idaatcha think it is rather the rainfall deficit. Regarding the causes of decline in yield, the analysis shows that the old Mahi and Ife have the perception that the prolonged drought, high winds and wildfires are the main while Idaatcha adults perceived that harmattan and wandering animals are the causes of yield loss. Ploughing followed by mowing in the late rainy season is the main coping strategy to mitigate the effects of climate change on the plantations of cashew. The contribution of research would be to put at the disposal of farmers planting material adapted to climate change.